ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL MATA KULIAH KALKULUS II BERDASARKAN TAKSONOMI SOLO PADA MAHASISWA JURUSAN PENDIDIKAN MATEMATIKA - A. Sriyanti; Mardhiah Mardhiah; Samriana Samriana; Munirah Munirah (Al Asma: Journal of Islamic Education, 2019)
The purpose of this study was to determine the types of mistakes made by students in complete matter of course calculus II and to determine the factors that led to student conduct in the matter in the course complete calculus II. This type of research is qualitative research to give matter in the form of diagnostic tests to the subject of research, in this case the second semester students majoring in mathematics education force in 2018 Faculty of Mathematics and Teaching UIN Alauddin Makassar. 5(five) respondents who were selected by the investigator based on the response rate obtained SOLO taxonomy students. Results showed the percentage of student response rates as follows: as much as 25.80% of the students are at prastructural response rate; 43.54% in the response rate unistructural; 24.19% in the response rate multistructural, 6.45% in the relational response rate and 0% of the students who are at the level of abstract extend the response, it was concluded that the second semester students majoring in mathematics education force in 2018 Faculty of Mathematics and Teaching UIN Alauddin Makassar is located the response rate unistructural. The cause of the students made a mistake in answering such questions, namely: the cause of the error to understand the concept is a theorem or formula that does not comply with the conditions precedent of the entry into force formula is not even able to write the right formula; the cause of the error is an error in entering data entering data into a variable and add data that is not needed in responding to a problem; cause misinterpretation of the language was a mistake in interpreting the symbols into the language of mathematics; the cause of the technical error is an error manipulate algebraic operations; as well as the cause of the error inference is inference statements do not correspond to logical reasoning.AbstrakTujuan penelitian ini adalah untuk mengetahui jenis-jenis kesalahan yang dilakukan mahasiswa dalam menyesaikan soal mata kuliah kalkulus II dan untuk mengetahui faktor-faktor yang menyebabkan mahasiwa melakukan dalam menyesaikan soal pada mata kuliah kalkulus II. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan memberikan soal dalam bentuk tes diagnostik kepada subjek penelitian, dalam hal ini mahasiswa semester 2 jurusan pendidikan matematika angkatan 2018 Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar. 5 (lima) orang responden yang dipilih oleh peneliti berdasarkan tingkat  respon taksonomi SOLO yang diperoleh  mahasiswa. Hasil penelitian diperoleh persentase tingkat respon mahasiswa sebagai berikut: sebanyak 25,80% dari jumlah mahasiswa berada pada tingkat respon prastruktural; 43,54% berada pada tingkat respon unistruktural; 24,19% berada pada tingkat respon multistruktural, 6,45% berada pada tingkat respon relasional serta 0% mahasiswa yang berada pada tingkat respon extend abstract, maka disimpulkan bahwa mahasiswa semester 2 jurusan pendidikan matematika angkatan 2018 Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar berada pada tingkat respon unistruktural. Penyebab mahasiswa melakukan kesalahan dalam menjawab soal-soal tersebut, yaitu: penyebab kesalahan memahami konsep adalah teorema atau rumus yang tidak sesuai dengan kondisi prasyarat berlakunya rumus tersebut bahkan tidak mampu menuliskan rumus yang tepat; penyebab kesalahan memasukkan data adalah kesalahan dalam memasukkan data ke variabel dan menambah data yang tidak diperlukan dalam menjawab suatu masalah; penyebab kesalahan interpretasi bahasa adalah kesalahan dalam menginterpretasikan simbol-simbol kedalam bahasa matematika; penyebab kesalahan teknis adalah kesalahan memanipulasi operasi aljabar; serta penyebab kesalahan penarikan kesimpulan adalah melakukan penyimpulan pernyataan yang tidak sesuai dengan penalaran logis.